DOES ETHNIC DIVERSITY AFFECT CUSTOMER SATISFACTION - Yuli Ardianto; M. Nuruddin Subhan; Dian Riskarini (INQUISITIVE : International Journal of Economic, 2020)
Important factors in a company related to ethical issues have an impact on consumer purchasing decisions. The relationship between the application of business ethics and purchasing decisions has been studied by several researchers. The impact of a business ethic and purchasing decisions and customer satisfaction depends on culture. The culture of ethnicity will form its own characteristics in the business that is carried out; it will impact how a consumer views the business which has an impact on satisfaction in purchasing. Culture also that can be seen from the ethnicity of the business owner will make customers consider buying products from a place of business. Therefore, the study wants to reveal how the visible culture or ethnicity can make customers satisfied to buy at a particular business. In addition, this study also aims to reveal how ethnicity can distinguish the relationshipship between ethical behavior and consumer satisfaction in making purchases. The methodology of the study is the content analysis method by conducting a content analysis on literature studies to obtain the results of the discussion of the selected variables. This study explores previous research related to building initial hypotheses without empirical data collection. The research results found that there is a relationshipship between ethnicity and consumer satisfaction. There are several opportunities to extend this study. This study could also be conducted by including motivation variables to moderate the relationship between ethnicity and customer satisfaction.